The influence of outcome expectations and willingness to seek counseling among students - Ibrahim, Ruziliza; Ahmad, Jamaludin (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The purpose of this study was to examine the influence of outcome expectations and willingness to seek counselling among undergraduate students in University Putra Malaysia (UPM). The total of N=160 undergraduate students from faculties of; Forestry, Economics and Management, Food Science and Technology and Medical and Health Science are randomly selected in the study. Among the participants 121 are female students and 39 were male students. The instruments used in this study were Disclosure Expectation Scale developed by Vogel and Wester (2003) and The Intention to Seek Counseling Inventory which is developed by Cash, Begley, McCown and Weise (1975). Researcher applied back translation technique to translate these instruments into Malay language. The obtained data n were analyzed by using descriptive statistic, the Pearson Correlation, t-test and one way ANOVA. The result of the study indicated that outcome expectation influences the willingness to seek counseling among students. The finding of the study also showed that there is no significant difference on outcome expectations and willingness to seek counselling between male and female students. But there was a difference on willingness to seek counselling between faculties. Generally, the findings of the study showed that UPM undergraduate students are willing to seek counselling.